Analisis Koloni Bakteri terhadap Pemberian Probiotik Komersial pada Air Buangan Industri Tahu - Budi Utomo; Solichin Solichin; Fazrul Fauzan Munadi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Indonesia boasts a number of tofu processing facilities totaling, around 84,000 both scale and large scale operations. These facilities collectively consume 2.56 million tons of soybeans each year. The high volume of tofu production poses a threat to the environment due to the generation of waste. If this waste is directly released into water bodies it can alter the waters characteristics potentially harming life. To address this issue Tofu Industry Wastewater can be implemented by introducing probiotics containing microorganisms that aid in breaking down matter and other components in the waste. This study focuses on analyzing bacterial colonies in Tofu Industry Wastewater by examining bacterial colonies present in these products. Various mixtures of Tofu Industry Wastewater and commercial probiotics will be tested at ratios of 1:1, 1:2, 1:3, and 1:4 over time periods ranging from 24, 48, 72, 96, 120, and 144 hours. The findings indicate that incorporating probiotics into Tofu Industry Wastewater can lead to a reduction in pollution levels.